2015
DOI: 10.1001/jamaophthalmol.2015.0814
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic Characterization of Complement Factor H R1210C Rare Genetic Variant in Age-Related Macular Degeneration

Abstract: IMPORTANCE The complement factor H R1210C rare variant confers the strongest genetic risk for age-related macular degeneration and earlier age at onset; however, its associated phenotype has not been well characterized. OBJECTIVE To describe specific fundus features of a white population with the R1210C rare variant. DESIGN, SETTING, AND PARTICIPANTS Fundus features specific for diagnosis and disease staging were retrospectively characterized by systematic review of all available fundus images for each pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(54 citation statements)
references
References 46 publications
(58 reference statements)
2
50
1
1
Order By: Relevance
“…In addition to these variants being associated with more advanced AMD within these families, carriers also had earlier age of onset of advanced disease (mean age = 59.2) compared to individuals with advanced AMD without rare CFH variants (mean age at diagnosis in our AMD database = 69.6, n = 1,627)26. We also explored disease symmetry, and among affected individuals carrying a rare CFH variant in these families, 75% (n = 9 of 12 carriers) exhibited a symmetric fundus phenotype.…”
Section: Resultsmentioning
confidence: 86%
“…In addition to these variants being associated with more advanced AMD within these families, carriers also had earlier age of onset of advanced disease (mean age = 59.2) compared to individuals with advanced AMD without rare CFH variants (mean age at diagnosis in our AMD database = 69.6, n = 1,627)26. We also explored disease symmetry, and among affected individuals carrying a rare CFH variant in these families, 75% (n = 9 of 12 carriers) exhibited a symmetric fundus phenotype.…”
Section: Resultsmentioning
confidence: 86%
“…R1210C is also associated with atypical hemolytic uremic syndrome (OMIM 134371). The drusen phenotype associated with the R1210C risk allele has recently been described (Ferrara and Seddon, 2015). The authors identified widespread soft drusen, both at the macular and outside the arcades, an unusual combination as such drusen are rarely observed in the peripheral retina.…”
Section: Complement and Drusenmentioning
confidence: 93%
“…Carriers of rare variants appear to have differing phenotypes compared with non-carriers. A number of studies have shown rare variants to be associated with earlier onset of advanced AMD [48,58,59,62,63]. Carriers of rare CFH variants have increased drusen load, are more likely to have extramacular drusen, drusen nasal to the optic disc, and crystalline or calcified drusen [62,63,64].…”
Section: Rare Variantsmentioning
confidence: 99%
“…A number of studies have shown rare variants to be associated with earlier onset of advanced AMD [48,58,59,62,63]. Carriers of rare CFH variants have increased drusen load, are more likely to have extramacular drusen, drusen nasal to the optic disc, and crystalline or calcified drusen [62,63,64]. In addition, rare variants in CFH, CFI, C9, and C3 have been more frequently observed in patients with GA than those with nvAMD [58,63].…”
Section: Rare Variantsmentioning
confidence: 99%